Comparative Analysis of Single-row and Double-row Arthroscopic Shoulder Rotator Cuff Repair: Impacts on Patient-reported Outcomes, Strength, and Range of Motion - Abrar H Mekkamannil; Jeganathan Parthiban; Suresh Perumal; Sanjay A K; Rohit KR (Journal of Orthopedics and Joint Surgery)
Background: Rotator cuff tears are a common clinical issue that often require surgical repair when nonsurgical treatment fails to improve symptoms. Arthroscopic repair techniques, including single-row (SR) and double-row (DR) repairs, offer several advantages over open surgery. SR repairs use one row of suture anchors, while DR repairs provide dual fixation on the humerus and within the rotator cuff. Variability exists within each fixation category based on factors such as suture type, number, configuration, anchor number, and placement location. Aim: This study aimed to assess and compare the strength, range of motion, and patient-reported outcome measures [Disabilities of the Arm, Shoulder, and Hand (DASH) score] in patients who underwent arthroscopic shoulder rotator cuff repair using either an SR or DR technique. The hypothesis was that the DR technique would yield superior results compared to the SR technique in terms of these three outcomes 1-year postsurgery. Materials and methods: An observational study was conducted at Sri Ramachandra Medical College from April 2022 to January 2024, involving 20 participants (12 male, 8 female) aged between 35 and 50 years. Patients underwent either SR or DR repair based on predefined inclusion and exclusion criteria. After obtaining informed consent, the participants were assessed preoperatively and postoperatively for abduction strength, range of motion, and DASH score on the day of admission, 3, 6, and 12 months after surgery. Comparative analysis of the outcomes between the SR and DR repair groups was performed using appropriate statistical methods (t-test) to identify any significant differences. Results: The DR group showed significantly better DASH scores at 3 and 6 months postoperatively compared to the SR group (p = 0.0014 and 0.003), with no significant difference at 1 year (p = 0.238). Abduction strength was significantly higher for DR repair at 3 and 6 months (p = 0.0024 and 0.0039), with both groups achieving similar strength at 1 year. The SR group demonstrated significantly better flexion, abduction, internal rotation, and external rotation at 3 and 6 months (p < 0.05), with both groups achieving almost the same range of motion 1-year postsurgery. Discussion: The study’s findings indicate that during the early postoperative phase, the DR technique produced better results in terms of DASH scores and abduction strength, while the SR technique showed better recovery of range of motion. These results are consistent with previous studies that found improved patient-reported outcomes and strength recovery with the DR approach, possibly due to enhanced footprint coverage and initial fixation strength. However, the better early range of motion recovery in the SR group contrasts with some studies that found no significant differences between the two techniques. This disparity may be attributed to variations in tendon quality, tear characteristics, and surgical techniques among the study populations. By 12 months postsurgery, both groups had equivalent range of motion and abduction strength, suggesting that initial differences in recovery may diminish with rehabilitation. The study’s limitations include a small sample size, lack of randomization, and potential confounding factors that may have influenced the outcomes. Conclusion: In the early postoperative phase, the DR technique demonstrated improved patient-reported outcomes and abduction strength, while the SR technique showed better recovery of range of motion. However, by 12 months postsurgery, both groups had similar results in terms of range of motion and abduction strength across all measured planes. When selecting the optimal repair technique, patient-specific characteristics should be considered, and the potential benefits of the DR technique should be weighed against the increased surgical time, cost, and risk of complications. Future research with larger, randomized samples and long-term follow-up is needed to validate these findings and guide clinical decision-making.